Chromosomal Aneuploidy Affects the Global Proteome Equilibrium of Colorectal Cancer Cells - Timo Gemoll; Jens K. Habermann; Susanne Becker; Silke Szymczak; Madhvi B. Upender; Hans-Peter Bruch; Ulf Hellman; Thomas Ried; Gert Auer; Hans Jörnvall; Uwe J. Roblick (Analytical Cellular Pathology)
Background: Chromosomal aneuploidy has been identified as a prognostic factor in the majority of sporadic carcinomas. However, it is not known how chromosomal aneuploidy affects chromosome-specific protein expression in particular, and the cellular proteome equilibrium in general.